Serum DNase1, sTNFR1 and sTNFR2 as Risk Factors for Lupus Nephritis in Systemic Lupus Erythematosus Patients - Manuaba, Ida Ayu Ratih Wulansari; Suryana, Ketut; Bakta, I Made; Sudarmaja, I Made (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Early detection and management of lupus nephritis (LN) in systemic lupus erythematosus (SLE) are essential to prevent irreversible kidney damage and improve patient outcomes; therefore, identifying reliable biomarkers to predict LN is paramount. However, there are still relatively few studies examining the potential biomarkers for LN in SLE patients. This study was conducted to investigate serum deoxyribonuclease I (DNase), soluble tumor necrosing factor 1 (sTNFR1) and soluble tumor necrosing factor 2 (sTNFR2) as a risk factor for LN in SLE patients.METHODS: A case-control study involving SLE patients aged 20-60 years was conducted. Blood was withdrawn from each subject for the measurement of serum level of DNase1, sTNFR1, and sTNFR2 that was performed using enzyme-linked immunoassay (ELISA) methods. Data was then analyzed using Chi-Square test and logistic regression tests.RESULTS: A total of 22 patients with LN and 22 without LN were included. The cut-off value for DNase1, sTNFR1, and sTNFR2 were 5.05 ng/mL, 6.52 ng/mL, and 7.02 ng/mL, respectively. The risk factors of LN in SLE patients were the low level of serum DNase1 (aOR=6.64; 95%CI: 1.25-35.29; p=0.026), low level of serum sTNFR1 (aOR=8.12; 95% CI: 1.56-42.10; p=0.013), and low level of serum sTNFR2 (aOR=5.57; 95%CI: 1.03-30.11; p=0.046).CONCLUSION: Serum DNase1 lower than 5.05 ng/mL, sTNFR1 lower than 6.52 ng/mL, and sTNFR2 lower than 7.02 ng/mL were risk factors for lupus nephritis in SLE patients. Hence, serum DNase1, sTNFR1 and sTNFR2 could be used as risk factors predictors for LN in SLE patients.KEYWORDS: DNase1, sTNFR1, sTNFR2, SLE, lupus nephritis